Differential RD-1-specific IFN-γ host responses to diverse Mycobacterium tuberculosis strains in HIV-uninfected persons may be explained by genotypic variation in the ESX-1 region. (July 2020) - Tomasicchio, Michele; Limberis, Jason; van der Merwe, Ruben; Jacobson, Rachael; Meldau, Richard; Theron, Grant; Nicol, Mark; Warren, Rob; Dheda, Keertan
Highlights: In a high TB burden and HIV prevalence setting we show that different M.tb strains are associated with different host-specific IFN-γ responses. We show that these strain-specific differences in host IFN-γ responses may be associated with mutations in the ESX-1 region. Our data have implications for IGRA assay interpretation and provide another reason for variability in IGRA responses and help to explain the differences seen between different IGRA formats. Abstract: Objectives: Between-person variability in T-cell-specific interferon-gamma release assay (IGRA) responses and discordance between IGRA test formats are poorly understood. Methods: We evaluated the IFN-γ responses (QuantiFERON-TB Gold-In-Tube [QFT-GIT] and TSPOT-TB) stratified according to the Mycobacterium tuberculosis spoligotype of the culture isolate obtained from the same patients with confirmed active tuberculosis (n = 91). We further analysed differences within the RD-1-encoding ESX-1 region between the different strain types using whole genome sequencing. Results: In HIV-uninfected patients, TSPOT.TB and QFT-GIT IFN-γ responses were 5-fold (p < 0.01) and 2-fold higher (p < 0.05) for those infected with family 33 compared to the LAM strain (additionally, TSPOT.TB responses were 5.6-fold [p < 0.05] and 2.6-fold higher [p < 0.05] for the patients infected with the family 33 versus the X strain and Beijing versus the LAM strain, respectively). Multivariate analysis revealed that strain type (determined by spoligotyping) was independently associated with the magnitude of the IGRA response (varied by IGRA test type) and this is likely explained by variability in the ESX-1 region of Mycobacteriumtuberculosis (determined by next-generation sequencing). Conclusions: These data have implications for the understanding of between-person heterogeneity in IGRA responses, Mycobateriumtuberculosis -specific host immunity, and the discordance between different IGRA test formats.